Effect of Computer Based Visualization on Students’ Cognitive Processes in Education Process - Bilbokaitė, Renata (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Objectivized phenomenon in science education and their elements, revealed for students in the homogenized visual form, stimulate development of the Subject consciousness within the context of learning. Visualization is visual artefact represented in visual way aiming to code or decode information. By stressing this, the use of visualization during lessons of Biology, Physics, Geography and Mathematics becomes very important – it helps for perception, attention, memory and imagination that are needed during learning processes. This article encloses empirical data about effect of computer based visualization on students’ cognitive processes. There were asked 2708 ninth and tenth form classes students in Lithuania. The results show that visualization is useful homogenously both for males and females, but females statistically significantly are sure about the positive effect of visual artifacts in the classroom.